Floral tissue of Petunia hybrida (V30) expresses only one member of the chalcone synthase multigene family. - Koes, R E (1986)
Twenty independent, petal-specific chalcone synthase (CHS) cDNA clones have been isolated from Petunia hybrida variety Violet 30 (V30). Sequence analysis shows that the largest of these clones contains the entire coding sequence. Using this clone in Southern blot analysis reveals the presence of multiple CHS gene copies in the genome of Petunia hybrida V30. Hybridization and sequence analysis of the CHS cDNA clones shows that they are all copied from a single mRNA species. This indicates the presence of only one transcriptionally active CHS gene in petals. Finally we report the identification, cloning and partial characterization of this gene.